New Therapeutic Strategy for Amino Acid Medicine: Effects of Dietary Glutamate on Gut and Brain Function - Akihiko Kitamura; Tomokazu Tsurugizawa; Akira Uematsu; Kunio Torii; Hisayuki Uneyama (Elsevier, 2012)
The gustatory and visceral stimulation from food regulates digestion and nutrient utilization, and free glutamate (Glu) release from food is responsible for the umami taste perception that increases food palatability. The results of recent studies reveal a variety of physiological roles for Glu. For example, luminal applications of Glu into the mouth, stomach, and intestine increase the afferent nerve activities of the glossopharyngeal nerve, the gastric branch of the vagus nerve, and the celiac branch of the vagus nerve, respectively. Additionally, luminal Glu evokes efferent nerve activation of each branch of the abdominal vagus nerve. The intragastric administration of Glu activates several brain areas (e.g., insular cortex, limbic system, and hypothalamus) and has been shown to induce flavor-preference learning in rats. Functional magnetic resonance imaging of rats has shown that the intragastric administration of Glu activates the nucleus tractus solitarius, amygdala, and lateral hypothalamus. In addition, Glu may increase flavor preference as a result of its postingestive effect. Considering these results, we propose that dietary Glu functions as a signal for the regulation of the gastrointestinal tract via the gut-brain axis and contributes to the maintenance of a healthy life. Keywords:: monosodium L-glutamate, vagus nerve, autonomic reflex, postingestive effect, functional magnetic resonance imaging, amino acid